FENOMENA GUGAT-MENGGUGAT PASCA HASIL PENGHITUNGAN SUARA PADA PILKADA SERENTAK 2015 - Askarial Askarial (PUBLIKA : Jurnal Ilmu Administrasi Publik, 2018)
Post-Reformation has caused some political consequences including reform of the system through the 1945 amendments were followed by the derivation of the form of laws and regulations in order to rebuild the political rights of the people who had experience of depoliticization, as well as local elections direct the newly held precisely on December 9, 2015 and is one way to build local politics.However, after the implementation of vote counting stages, there is still a stage set by law to candidates who feel of elections has not run well, can menyampaikann lawsuit to the Constitutional Court (MK) .In Court Rules only limit lawsuit related to the difference between the voting results only , but this limit could not stem the applicant seeking keadilan.Puluhan petition effort also contain indications of fraud reasons pilkada structured, systematic and massive. As mobiliasasi mass, money politics to support one party to the two pairs of candidates.